2019
DOI: 10.1016/j.jmmm.2018.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Nature of magnetoelectric coupling in corundum antiferromagnet Co4Ta2O9

Abstract: We study the magnetocapacitance (MC) effect and magnetoelectric (ME) coupling in spin-flop driven antiferromagnet Co 4 Ta 2 O 9 . The magnetocapacitance data at high magnetic fields are analyzed by phenomenological Ginzburg-landau theory of ferroelectromagnets and it is found that change in dielectric constant is proportional to the square of magnetization. The saturation polarization and magnetoelectric coupling are estimated to be 52µC/m 2 and γ = 1.4 x10 -3 (emu/g) -2 respectively at 6 Tesla. Electric polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
4
15
1
Order By: Relevance
“…2c. Note that this result is different from the previous results on polycrystalline samples, where the spin-flop transition occurs at a higher H of ~ 0.9 T, possibly due to the averaging effect over grain orientations 31 . On the other hand, the M c increases almost linearly up to 9 T resulting in a magnetic moment of ~ 2.1 μ B /f.u.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…2c. Note that this result is different from the previous results on polycrystalline samples, where the spin-flop transition occurs at a higher H of ~ 0.9 T, possibly due to the averaging effect over grain orientations 31 . On the other hand, the M c increases almost linearly up to 9 T resulting in a magnetic moment of ~ 2.1 μ B /f.u.…”
Section: Resultscontrasting
confidence: 99%
“…Further studies of the magnetoelectric effect in honeycomb lattices were done on the isostructural compound Co 4 Ta 2 O 9 (CTO) 6,30,31 . In CTO, the antiferromagnetic order emerges at T N ≈ 20 K, simultaneously with the appearance of a dielectric anomaly and a ferroelectric polarization in applied magnetic fields.…”
Section: Strongly Correlated Materials With Multiple Order Parametersmentioning
confidence: 99%
“…The space group is trigonal P 3 c 1 (No. 165) consistent with a recent report 12 . There are two crystallographically distinct sites occupied by the Co 2+ ions.…”
Section: Introductionsupporting
confidence: 90%
“…The origin of the distinct ME effects in these two compounds, therefore, deserves a detailed investigation. The magnetic structure of Co 4 Ta 2 O 9 has been recently determined by neutron powder diffraction 12 . It proposed a noncollinear magnetic structure in the ab-plane, similar to the one de-termined for Co 4 Nb 2 O 9 14,15 in the same magnetic space group, C2/c .…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Deng et al showed that the magnetic moments of Co atoms are noncollinearly arranged in the ab plane [23]. A recent neutron-diffraction study on Co 4 Ta 2 O 9 also evidenced noncollinearly canted spin arrangement of Co atoms in the ab plane [24].…”
Section: Discussionmentioning
confidence: 99%